Prospects for Increasing the Economic Independence of the Community Through the Red and White Cooperative Based on Maqashid Sharia - Muslim Marpaung; Faisal; Muflihul Fadhil; Tedi Hermansyah (International Journal of Economics Accounting and Management, 2026)
The purpose of this research is to examine the impact of capital structure, profitability, and liquidity on stock returns, taking into account company size as a moderating factor, in food and beverage firms listed on the Indonesia Stock Exchange (BEI) between 2019 and 2023. Data from the Indonesia Stock Exchange served as the foundation for this research. The sampling technique employed was purposive sampling. This research included a sample of 11 companies from the food and beverage sub-sector listed on the Indonesia Stock Exchange between 2019 and 2023, with a total of 55 companies. Moderated Regression Analysis (MRA), secondary data, and panel data regression analysis were the methods used. According to the findings of this study, capital structure has a positive and considerable impact on share returns, liquidity has a positive and significant impact on share returns, and profitability has no effect on share returns. The impact of profitability on stock returns is not greatly moderated (strengthened) by firm size